Effect on long-term average spectrum of pop singers' vocal warm-up with vocal function exercises. (April 2013) - Guzman, Marco; Angulo, Mabel; Muñoz, Daniel; Mayerhoff, Ross
Abstract This case-control study aimed to investigate if there is any change on the spectral slope declination immediately after vocal function exercises (VFE) vs traditional vocal warm-up exercises in normal singers. Thirty-eight pop singers with perceptually normal voices were divided into two groups: an experimental group (n = 20) and a control group (n = 18). One single session with VFE for the experimental group and traditional singing warm-up exercises for the control group was applied. Voice was recorded before and after the exercises. The recorded tasks were to read a phonetically balanced text and to sing a song. Long-term average spectrum (LTAS) analysis included alpha ratio, L1–L0 ratio, and singing power ratio (SPR). Acoustic parameters of voice samples pre- and post-training were compared. Comparison between VFE and control group was also performed. Significant changes after treatment included the alpha ratio and singing power ratio in speaking voice, and SPR in the singing voice for VFE group. The traditional vocal warm-up of the control group also showed pre–post changes. Significant differences between VFE group and control group for alpha ratio and SPR were found in speaking voice samples. This study demonstrates that VFE have an immediate effect on the spectrum of the voice, specifically a decrease on the spectral slope declination. The results of this study provide support for the advantageous effect of VFE as vocal warm-up on voice quality.